Analisis Perbandingan Return Saham dan Volume Perdagangan Sebelum dan Selama January Effect pada Saham Kapitalisasi Besar dan Kecil - Erica Fahmi Aprillia (Fakultas Ekonomi dan Bisnis, 2025)
This study aims to analyze the comparison of stock returns and trading volume on large and small capitalization stocks before and during the January Effect phenomenon. The January Effect is a market anomaly characterized by a tendency for stock prices to rise in January. This study uses secondary data in the form of daily stock prices and market capitalization of companies listed on the Indonesia Stock Exchange (IDX) during the 2023–2025 period. The sample was selected using purposive sampling, consisting of 20 stocks representing large and small capitalization. The analytical methods used include descriptive statistics, the Kolmogorov-Smirnov normality test, and the Wilcoxon Signed Ranks Test. The results show that there is no significant difference in stock returns for both large and small capitalizations before and during the January Effect, as indicated by significance values greater than 0.05. However, a significant difference is found in the trading volume of large-cap stocks, while small-cap stocks show no such difference. These findings support the Efficient Market Hypothesis, which asserts that stock prices reflect all available information, making it unlikely to gain abnormal profits from seasonal patterns like the January Effect.
Reupload Repository hasyim Mei 2026 :: Finalisasi Repositori File 25 Mei 2026_Kurnadi
Keywords: Stock Return; Trading Volume; Large Capitalization; Small Capitalization; January Effect.